Relevansi Konsep Ta'dib Dalam Filsafat Pendidikan Islam Kontemporer - Lulu Fatkhatul Jannah; Muhammad Sendi Saputra; Syifaul Firha Zaen (CV. ITTC INDONESIA, 2026)
This study examines the relevance of the concept of ta’dib in contemporary education, which faces challenges such as moral crises, secularization, and the reduction of education to mere knowledge transfer. The aim of this research is to reanalyze the position of ta’dib as an educational paradigm emphasizing the formation of adab in the modern context. The method employed is a literature review with a conceptual analysis approach toward relevant literature and the thoughts of Islamic education scholars. The findings indicate that ta’dib remains highly relevant in addressing contemporary educational issues, as it integrates cognitive, affective, and spiritual dimensions holistically. It not only emphasizes knowledge acquisition but also character building and ethical awareness grounded in Islamic values. Therefore, ta’dib can serve as an alternative paradigm for developing a more holistic and character-oriented education system in the context of modernity